The Reducing Agents in Sonochemical Reactions without Any Additives - Kyuichi Yasui (Molecules, 2023)
It has been experimentally reported that not only oxidation reactions but also reduction reactions occur in aqueous solutions under ultrasound without any additives. According to the numerical simulations of chemical reactions inside an air or argon bubble in water without any additives under ultrasound, reducing agents produced from the bubbles are <semantics>H, H2, HO2</semantics> (which becomes superoxide anion (<semantics><msubsup>O2−</msubsup></semantics>) in liquid water), <semantics>NO</semantics>, and <semantics>HNO2</semantics> (which becomes <semantics><msubsup>NO2−</msubsup></semantics> in liquid water). In addition, <semantics>H2O2</semantics> sometimes works as a reducing agent. As the reduction potentials of <semantics>H</semantics> and <semantics>H2</semantics> (in strongly alkaline solutions for <semantics>H2</semantics>) are higher than those of <semantics>RCHOH</semantics> radicals, which are usually used to reduce metal ions, <semantics>H</semantics> and <semantics>H2</semantics> generated from cavitation bubbles are expected to reduce metal ions to produce metal nanoparticles (in strongly alkaline solutions for <semantics>H2</semantics> to work). It is possible that the superoxide anion (<semantics><msubsup>O2−</msubsup></semantics>) also plays some role in the sonochemical reduction of some solutes. In strongly alkaline solutions, hydrated electrons (<semantics>e−<mfenced>aq</mfenced></semantics>) formed from <semantics>H</semantics> atoms in liquid water may play an important role in the sonochemical reduction of solutes because the reduction potential is extremely high. The influence of ultrasonic frequency on the amount of <semantics>H</semantics> atoms produced from a cavitation bubble is also discussed.